Perencanaan Sumber Daya Manusia dalam Pengembangan Kompetensi Lingkungan Karyawan untuk Mendukung Decent Work dan Climate Action - Sheila Fairuz Nissa; Nabila Dwi Amalia; Novelia Muzallifah (Pusat Riset dan Inovasi Nasional, 2026)
The development of climate change issues and the growing awareness of environmental sustainability have encouraged organizations to pay greater attention to human resource management that emphasizes not only productivity but also environmental sustainability. This study aims to examine human resource planning in developing employees' environmental competencies to support Decent Work and Climate Action. The study employed a Systematic Literature Review (SLR) method by collecting and analyzing relevant studies published between 2020 and 2025 from Google Scholar, SINTA, and ResearchGate. The findings indicate that human resource planning plays a significant role in developing environmental competencies through training programs, the enhancement of green skills, and the implementation of Green Human Resource Management (GHRM) practices. The development of environmental competencies enhances employees' environmental awareness, attitudes, and pro-environmental behaviors, thereby supporting organizational sustainability. Furthermore, the implementation of Decent Work through improved employee welfare, social protection, and workforce quality development constitutes an essential component of effective human resource management. Therefore, integrating environmental competencies into human resource planning contributes to organizational sustainability while supporting the achievement of sustainable development goals related to Decent Work and Climate Action.